The Eolie Islands' Mollicas : a family history - Mollica, Maurice ([Avondale Heights, Victoria] : Maurice Mollica, 2019)
Annotation. Author Maurice Mollica has researched the history of the Mollica family who were born on the Eolie Islands. The family go back many centuries and now many live in Australia and the United States.
Includes index.
Keywords: Mollica family; Italians -- Victoria -- Genealogy; Lipari Islands (Italy) -- Genealogy; Australian